Prenatal exposure to modafinil alters behavioural response to methamphetamine in adult male mice - Ruda-Kucerova, Jana; Pistovcakova, Jana; Amchova, Petra; Sulcova, Alexandra; Machalova, Alena (International journal of developmental neuroscience, 2018)
Modafinil is a psychostimulant drug prescribed for treatment of narcolepsy. However, it is used as a "smart drug" especially by young adults to increase wakefulness, concentration and mental performance. Therefore, it can also be used by women with childbearing potential and its developmental effects can become a concern. The aim of this study was to assess behavioural and immune effects of prenatal modafinil exposure in mice and to evaluate the reaction to methamphetamine exposure on these animals in adult age. Pregnant female mice were given either saline or modafinil (50 mg/kg orally) from gestation day (GD) 3 to GD 10 and then a challenge dose on GD 17. The male offspring were treated analogously at the age of 10 weeks with methamphetamine (2.5 mg/kg orally). Changes in the spontaneous locomotor/exploratory behaviour and anxiogenic profile in the open field test were assessed in naïve animals, after an acute and 8th modafinil dose and the challenge dose following a 7-day wash-out period. One month after completion of the behavioural study, the leukocyte phagocytosis was examined by zymosan induced and luminol-aided chemiluminiscence assay in vitro. The modafinil prenatally exposed mice showed basal hypolocomotion, increased anxiety, lower locomotor effect of acute methamphetamine and increased vulnerability to behavioural sensitization. The leukocyte activity did not show significant differences. Prenatal modafinil exposure alters basal behavioural profile, decreases acute effect of methamphetamine and enhances vulnerability to development of behavioural sensitization at adulthood. This may lead to higher vulnerability to development of addiction.
Keywords: methamfetamin; gestační stáří; Analysis of Variance; Animals; novorozená zvířata; Methamphetamine; Female; Age Factors; Gestational Age; ženské pohlaví; benzhydrylové sloučeniny; pohybová aktivita; Animals, Newborn; věkové faktory; Wakefulness-Promoting Agents; Mice; těhotenství; Exploratory Behavior; Locomotion; zpožděný efekt prenatální expozice; myši; leukocyty; stimulancia; lokomoce; analýza rozptylu; Benzhydryl Compounds; Male; fagocytóza; Leukocytes; Mice, Inbred ICR; Phagocytosis; Prenatal Exposure Delayed Effects; myši inbrední ICR; Motor Activity; pátrací chování; stimulanty centrálního nervového systému; zvířata; mužské pohlaví; Pregnancy; Central Nervous System Stimulants